AB0413 THE PROSPECTIVE ASSESSMENT OF RITUXIMAB AND TOCILIZUMAB TREATMENT EFFECT ON RF-IGM AND ACPA TITRES IN RHEUMATOID ARTHRITIS PATIENTS. (June 2019) - Borys, Olga; Targonska-Stepniak, Bozena; Dryglewska, Magdalena; Majdan, Maria
Abstract : Background: Rheumatoid arthritis (RA) is associated with several specific autoantibodies, which can be used as diagnostic and prognostic markers. These include rheumatoid factor IgM (RF-IgM) and anti-citrullinated protein autoantibodies (ACPA). The data reporting an impact of biological disease modifying anti-rheumatic drugs (bDMARDs) on RA serological markers are divergent, probably depending on the type of treatment. Objectives: The goal of this study was to prospectively evaluate the impact of bDMARDs [rituximab (RTX) and tocilizumab (TCZ)] on titers of RA serological markers (RF IgM, ACPA), in correlation with the disease activity assessment. Methods: The study was conducted in the consecutive 42 patients with RA (36 women, 6 men), with the mean (SD) age 48.9 (13.8) and disease duration 9.2 (3.8) years. The treatment with RTX was administered to 30 patients and with TCZ to 12 patients. The following parameters were assessed for all patients: joint counts, disease activity index of 28 joints (DAS28), complete blood cell counts, erythrocyte sedimentation rate (ESR), serum concentration of serum amyloid A (SAA), RF-IgM, ACPA. Blood samples were taken before the drug administration (baseline) and in consecutive months (3, 6 and 9 months). Results: Parameters of the disease activity decreased significantly in consecutive months, in comparison with the baseline assessment, in both treatment groups. The mean (SD) DAS28 decreased significantly in both groups (RTX and TCZ): respectively at baseline: 5.75 (0.69) and 5.47 (0.51); month 3: 3.92 (1.13) and 2.84 (0.76); month 6: 3.23 (1.09) and 2.3 (0.94); month 9: 3.67 (1.19) and 2.12 (0.81). The mean (SD) SAA concentration was significantly lower in consecutive months, in both groups (RTX and TCZ): respectively at baseline: 408.5 (268.2) and 402.0 (291.0) ug/ml; month 3: 214.2 (255.3) and 83.6 (157.8) ug/ml; month 6: 100.2 (154.9) and 31.5 (46.3) ug/ml; month 9: 108.5 (128.8) and 26.7 (32.4) ug/ml. The significant reduction of RA specific autoantibodies (RF-IgM and ACPA) was noted in the group of patients treated with RTX (Figure 1, Figure 2 ). Treatment with TCZ did not affect significantly RA specific autoantibodies up to 6 months of therapy; the significant decrease of ACPA concentration was noted only between baseline and month 9 (Figure 3 ); no significant change of RF-IgM was observed (Figure 4 ). Conclusion: The results of the study suggest that both bDMARDs reduced significantly the disease activity in RA patients. The treatment with both drugs was associated with a significant reduction of SAA. However only RTX treatment affected significantly the production of disease specific autoantibodies. Long-term observation is necessary to assess a reliable effect of bDMARDs on the production of marker autoantibodies in association with the disease activity. Disclosure of Interests: Olga Borys: None declared, Bozena Targonska-Stepniak Speakers bureau: Sandoz, Berlin-Chemie, Magdalena Dryglewska: None declared, Maria Majdan Speakers bureau: MSD, UCB, Abbvie, Roche